PENGEMBANGAN MEDIA DIORAMA UNTUK MENINGKATKAN ANALISIS PERAN EKONOMI DALAM KEHIDUPAN SOSIAL SISWA SEKOLAH DASAR - Badriah, Anisatul; Imron, Ilmawati Fahmi; Laila, Alfi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The problem is the low motivation to learn in class V students in participating in learning. Lack of use of media in learning Social Sciences. As a result, students feel less enthusiastic and less enthusiastic about participating in learning. From these problems, researchers developed diorama learning media products with the aim of knowing the validity, effectiveness, and practicality of diorama media in social studies subjects. This research is a type of research and development (RnD) ADDIE model. The research and development steps for the ADDIE model consist of 5 five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used are questionnaires and document studies. Data collection techniques using interview instruments, questionnaires and tests. The data analysis technique used is a qualitative descriptive data analysis technique. The subject of the small-scale trial was 1 teacher and 14 students while in the large-scale trial there were 1 teacher and 26 students in one class. From the results of the KBK calculation, the evaluation questions on a small scale using diorama media at SDN Mrican 2 obtained a score of 36%. While the evaluation results on a large scale using diorama media at SDN Mrican 1 get a value of 88%. So it can be concluded that the evaluation results using diorama media are very feasible to assist in the learning process in the classroom